Answer:
[tex]A^c\cap B[/tex]
Step-by-step explanation:
Given,
U = {a, b, c, d}, A = {a, b} and B = {b, c},
[tex]A^c=U-A=\{c, d\}[/tex]
[tex]B^c=U-B = \{ a, d\}[/tex]
Thus,
[tex]A\cup B^c=\{a, b, d\}[/tex]
[tex]A\cap B = \{b\}[/tex]
[tex]A\cap B^c = \{a\}[/tex]
[tex]A^c\cap B = \{c\}[/tex]
[tex]A\cup B = \{a, b, c, d\}[/tex]
[tex]A^c\cup B = \{b, c, d\}[/tex]
[tex]A^c\cap B^c = \{d\}[/tex]
Now, two sets are called disjoint if there intersection is ∅,
By the above explanation it is clear that,
[tex](A\cup B^c)\cap (A^c\cap B) = \phi[/tex]
Hence, [tex] (A^c\cap B)[/tex] is disjoint to [tex](A\cap B^c)[/tex]